Cultural genocide - Davidson, Lawrence, 1945- (New Brunswick, N.J. : Rutgers University Press, 2012)
Annotation Most scholars of genocide focus on mass murder. Lawrence Davidson, by contrast, explores the murder of culture. He suggests that when people have limited knowledge of the culture outside of their own group, they are unable to accurately assess the alleged threat of others around them. Throughout history, dominant populations have often dealt with these fears through mass murder. However, the shock of the Holocaust now deters todays great powers from the practice of physical genocide. Majority populations, cognizant of outside pressure and knowing that they should not resort to mass murder, have turned instead to cultural genocide as a second best politically determined substitute for physical genocide. InCultural Genocide, this theory is applied to events in four settings, two events that preceded the Holocaust and two events that followed it: the destruction of American Indians by uninformed settlers who viewed these natives as inferior and were more intent on removing them from the frontier than annihilating them; the attack on the culture of Eastern European Jews living within Russian-controlled areas before the Holocaust; the Israeli attack on Palestinian culture; and the absorption of Tibet by the Peoples Republic of China. In conclusion, Davidson examines the mechanisms that may be used to combat todays cultural genocide as well as the contemporary social and political forces at work that must be overcome in the process.
Theoretical foundations -- Cultural genocide and the American Indians -- Russia and the Jews in the nineteenth century -- Israel and Palestinian cultural genocide -- The Chinese assimilation of Tibet -- Conclusion.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Ethnic conflict; Persecution -- Social aspects; Assimilation (Sociology); Indians, Treatment of -- North America -- History; Jews -- Russia -- Social conditions -- 19th century; Palestinian Arabs -- Israel -- Social conditions -- 20th century; Tibet Autonomous Region (China) -- Social conditions; Conflits ethniques; Persécutions -- Aspect social; Assimilation (Sociologie); Attitudes envers les Peuples autochtones -- Amérique du Nord -- Histoire; Juifs -- Russie -- Conditions sociales -- 19e siècle.; Région autonome du Tibet (Chine) -- Conditions sociales; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Ethnic Studies -- General; SOCIAL SCIENCE -- Minority Studies; HISTORY -- Modern -- 20th Century; Assimilation (Sociology); Ethnic conflict; Indians, Treatment of; Jews -- Social conditions; Russia; Social conditions; China -- Tibet Autonomous Region; Israel; North America; 1800-1999; History